Use of a Gouy-Chapman-Stern Model for Membrane-Surface Electrical Potential to Interpret Some Features of Mineral Rhizotoxicity. - Kinraide, T. B. (1994)
A consideration of mineral toxicity to roots only in terms of ion activities in the rooting medium can be misleading. A Gouy-Chapman-Stern model, by which relative ion activities at cell-membrane surfaces may be estimated, has been applied to problems of mineral rhizotoxicity, including the toxicity of Al3+, La3+, H+, Na+, and SeO42-, to wheat (Triticum aestivum L.) roots. The Gouy-Chapman portion of the model is expressed in the Grahame equation, which relates the charge density ([sigma]) and electrical potential (E0) at the surface of a membrane to the concentrations of ions in a contracting bulk solution. The Stern modification of the theory takes into account changes in [sigma] caused by ion binding at the membrane surface. Several theoretical problems with the model and its use are considered, including the fact that previous authors have usually related the physiological effects of an ion at a membrane surface to the computed concentration (Ci0) of the unbound ion rather than its computed activity (ai0). This practice implies the false assumption that Ci0 is proportional to ai0. It is demonstrated here that ai0, computed from external activities (ai[infinity symbol]) by a Nernst equation [ai0 = ai[infinity symbol]exp([mdash]ZiFE0/RT), where Zi is the charge on the ion, F is the Faraday constant, R is the gas constant, and T is the temperature], correlates well with ion toxicity and that Ci0 sometimes correlates poorly. These conclusions also apply to issues of mineral nutrition.